Impact of the interconnection of cross-border electricity markets in the expansion of the generation parks of Peru and Ecuador - Jara Caytuiro, Fabiola (2021)
In the last years at international level the interconnection of electrical markets is being carried out, which makes it possible to optimize the use of energy resources and improve the reliability of the systems. This process of electrical integration generates a redistribution of benefits among agents, which also generates new problems for coordination and regulation, so there is a need to design new regulation policies based on analysis of the impacts of market interconnection. cross-border The objective of this article is to improve the understanding of the effects that interconnection will have on parameters such as: the evolution of the electricity generation park in each electrical system, the incorporation of large hydroelectric power plants especially in countries that have water complementarity and incorporation of power plants based on non-conventional renewable energy resources. To do this, a model has been structured that makes use of the theory of systems dynamics and the case of the Peru-Ecuador interconnection was analyzed, finding that the state policies previously applied in both countries have caused that the marginal costs of their systems they are relatively low, so that new generation would not enter in the short term; It was also concluded that although expanding hydroelectric capacity may seem the best solution given the water complementarity between the two countries, low marginal costs mean that the first plants to be installed are based on natural gas.